(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
The Use of Digital Marketing for Development of Potted Fruit Plants (Tabulampot) Business in Bali Province at Industrial Era 4.0. Digital marketing is a marketing technique utilizing digital technology that can adapt to market conditions in the industrial era 4.0. The purpose of the study was to determine the use of the digital marketing mix 4C, digital marketing platform used by potted fruit plants (tabulampot) businesses in Bali Province with a qualitative descriptive method, and analyze the relationship between convenience, content, response, security, and trust in product purchasing decisions in digital marketing for the tabulampot business in Bali Province using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of the study show 1) All tabulampot businesses have utilized the 4C digital marketing mix, although its implementation has not been maximized. 2) The most used digital marketiing platform by tabulampot businesses in Bali Province is Whatsapp and Google Business. 3) Convenience, content, response, and security have an insignificant relationship, while trust has a significant relationship with product purchase decisions in digital marketing tabulampot business in Bali Province. Based on these results, it is suggested that tabulampot entrepreneurs in Bali Province pay more attention to the currency aspect, use more types of digital marketing platforms, and also pay more attention to customer trust to marketing their products.